How has the shipping industry coped with the maritime labour convention? - Khoo, Sze Fan (2017)
Commonly known as the “fourth pillar” in the international shipping's regulatory regime, the Maritime Labour Convention (MLC) 2006 seeks to achieve both social and labour rights for seafarers in the maritime industry. MLC came into force on 13 August 2013 and has since then prompted the different stakeholders to implement changes in their respective spheres of responsibility. More specifically, flag states uphold and implement MLC standards into their national legislations, ship-owners re-look into employment policies and implement necessary changes to on-board working conditions, while the unions represent the well-being of seafarers, by reviewing seafarer’s employment agreement standards and collective bargaining agreement (CBA), and seek to provide a supportive role to ensure seafarers’ rights are upheld. This paper seeks to focus on the impact of MLC on the lives of seafarers 4 years after its implementation. The study determines which DMLC provisions provide tangible benefits to seafarers’ lives and discusses further areas of improvement that can be made to these provisions.